Exploring deception using automatically detected facial action units - Vinkemeier, Doratha (2020)
Lie detection has always gripped mankind. Today, applications range from individual employee screening to mass terror scenarios. Yet, signs of deception are still not well understood and there is general agreement that humans are bad at detecting them. We suffer from bias and subjectivity as well as a lack of stamina and observational acuity. For this reason, hope is now being placed on automatic methods such as action unit (AU) detectors, which detect facial muscle movements that can reveal affective states.